Investigation on effect of surface roughness pattern to dynamic performance of mems resonators in various types of gases and gas rarefaction - Thinh, Lam Minh; Truong, Phan Minh; Thang, Trinh Xuan; Thanh, Ngo Vo Ke; Cuong, Le Quoc; Cuong, Nguyen Chi (Vietnam Journal of Science and Technology, 2021)
The average modified molecular gas lubrication (MMGL) equation, which is modified with pressure flow factors and effective viscosity, is utilized to analyze the squeeze film damping (SFD) on micro-beam resonators considering effect of surface roughness pattern in various types of gases and gas rarefaction. Then, effect of surface roughness pattern (film thickness ratio and Peklenik number) is discussed on the quality factor (Q-factor) of micro-beam resonators in various types of gases and gas rarefaction. Thus, effect of surface roughness pattern is significantly reduced as effective viscosity of gas decreases in higher mode of resonator and higher gas rarefaction.